Impact of climate change on potential evapotranspiration and growing season in Mexico: Climate change and PET in Mexico - Monterroso-Rivas, Alejandro Ismael; Gómez-Díaz, Jesús David (REVISTA TERRA LATINOAMERICANA, 2021)
Potential evapotranspiration (PET) and length of growth period (LGP) are essential indicators of agricultural planning. National and local agendas should consider climate change scenarios and its impact on evapotranspiration. Therefore, the objective of this study was to analyze spatial distribution of PET and LGP in current climate conditions throughout the country, and under a climate change scenario to have suff icient technical elements for recommending adaptation actions for agricultural national production. The monthly PET was estimated from the reference PET (ET0) by the Penman-Monteith method using parameter and monthly average rainfall (R), start and end date, and length of growing period were evaluated. Once this was done, 28 climate change scenarios were studied to def ine the alteration of PET and its effect on LGP in the agricultural areas of the country. PET is expected to increase practically throughout the national territory as a consequence of the general increase in temperature and the decrease in relative humidity. PET classes smaller than 1000 mm per year may decrease, while those greater than 1000 mm may increase on average 20% around the years 2040-2069, and almost 50% towards 2070-2099. When climate change in LGP was considered for each state, three of them (Baja California Sur, Coahuila, and San Luís Potosí) were considered to experience no change concerning current conditions. In the rest of states, the LGP may decrease due to a combination of changes at the beginning and end of the growing period. Cartographic studies allow spatial analysis of the results, which should be integrated into the planning of agricultural water use. At the same time, they make it possible to advance in the design of measures to adapt for climate change with a solid technical support.